THE EFFECTIVENESS OF THE USE OF CHEMCOLLECTIVE VIRTUAL LABORATORY MEDIA WITH GUIDED INQUIRY LEARNING MODELS ON STUDENT LEARNING OUTCOMES ON ACID-BASE TITRATION MATERIAL - Theresia, Clara; Hartati, Yuli; Lestari, Sri (PROSIDING SEMINAR KIMIA, 2023)
This study aims to determine the effectiveness of using ChemCollective virtual laboratory media with guided inquiry learning models on student learning outcomes on acid-base titration material. The subjects of this study were XI MIA 1 and XI MIA 2 classes totaling 59 students. The research subjects were selected using saturated sampling technique. This research method is pre-experiment with one group pretest-posttest design. Data collection used tests in the form of pre-test and post-test and student response questionnaires which were then analyzed using the N-Gain test and effect size test. The results showed that the use of virtual laboratory media was effective for improving student learning outcomes with an N-Gain value of 0.5022 which was classified as moderate and the level of effectiveness was classified as very strong with an effect size value of 1.5716. Keywords: Effectiveness, Virtual Laboratory, Learning Outcomes, Acid-Base Titration